Social mobility in the Philippine labor market - Dacuycuy, Lawrence B. (The Philippine Review of Business and Economics, 2018)
In this paper, we focus on the measurement and characterization of social mobility in the Philippine labor market using standard methodologies. First, we ascertain the degree to which intergenerational wage mobility can be measured using available survey data. Second, using a simple regression based approach, we determine the extent to which wages are persistent on the part of sons and daughters relative to fathers? wage outcomes. Third, we highlight the role of parental education and measure how the labor market rewards or penalizes labor market participants. Fourth, we examine the statistical importance of parental educational achievements relative to their children using the ordered probability model. The paper finds wage persistence. Transition probabilities show that persistence is observed at the lowest and highest quintiles of the wage distribution. The transition probabilities show that persistence is not uniformly observed throughout the reference distribution. Returns to education among the well-educated sons and daughters remain high, and parental education continues to determine the relative magnitudes of wage gains and penalties. Children of highly educated fathers expectedly reap wage gains while those whose fathers have finished no more than high school education suffer from wage penalties. Parental education profiles determine a child?s educational achievements. Results indicate that children with college educated parents tend to graduate from college with high likelihood of success. In terms of resources, nonlabor income will only boost the probability of being a college graduate, with the rest of the education outcomes registering negative effects. Finally, consistent with the literature, children from non-poor households have higher likelihood to graduate from high school and college compared with their counterparts from poor households.